2017
DOI: 10.1038/s41419-017-0002-y
|View full text |Cite
|
Sign up to set email alerts
|

HRD1 prevents apoptosis in renal tubular epithelial cells by mediating eIF2α ubiquitylation and degradation

Abstract: Apoptosis of renal tubular epithelial cells is a key feature of the pathogenicity associated with tubulointerstitial fibrosis and other kidney diseases. One factor that regulates important cellular processes like apoptosis and cell proliferation is HRD1, an E3 ubiquitin ligase that acts by promoting ubiquitylation and degradation of its target protein. However, the detailed mechanisms by which HRD1 acts as a regulator of apoptosis in renal tubular epithelial cells have not been established. In our previous liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…31 Ubiquitination and degradation of a third negative signaling protein, eIF2α, by HRD1 prevent apoptosis in renal tubular cells. 28 We previously demonstrated that derlin-1 promotes ubiquitination and degradation of the epithelial sodium channel (ENaC), and we suggested that HUWE1 might act as an E3 ligase of α-ENaC.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…31 Ubiquitination and degradation of a third negative signaling protein, eIF2α, by HRD1 prevent apoptosis in renal tubular cells. 28 We previously demonstrated that derlin-1 promotes ubiquitination and degradation of the epithelial sodium channel (ENaC), and we suggested that HUWE1 might act as an E3 ligase of α-ENaC.…”
Section: Discussionmentioning
confidence: 95%
“…The degradation of the negative signaling protein Smad7 by ubiquitination leads to TGF‐β activation, while the ubiquitination and degradation of another negative signaling protein IκB, a protein that is suppressed by NFκB and that plays a critical role in renal disease, allows the nuclear translocation of NFκB for participation in gene transcription . Ubiquitination and degradation of a third negative signaling protein, eIF2α, by HRD1 prevent apoptosis in renal tubular cells . We previously demonstrated that derlin‐1 promotes ubiquitination and degradation of the epithelial sodium channel (ENaC), and we suggested that HUWE1 might act as an E3 ligase of α‐ENaC.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The first identified substrate of HRD1 was 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase (HMGCR), which is tightly regulated by metabolic feedback control (32). Later, it was reported that HRD1 also targets non-ERAD proteins to regulate various cellular processes (33)(34)(35)(36)(37)(38)(39) besides the ERAD component IRE1 (40). However, its involvement in lung tumorigenesis remains unknown.…”
mentioning
confidence: 99%